2023
DOI: 10.1002/jev2.12311
|View full text |Cite
|
Sign up to set email alerts
|

Accessory ESCRT‐III proteins are conserved and selective regulators of Rab11a‐exosome formation

Abstract: Exosomes are secreted nanovesicles with potent signalling activity that are initially formed as intraluminal vesicles (ILVs) in late Rab7‐positive multivesicular endosomes, and also in recycling Rab11a‐positive endosomes, particularly under some forms of nutrient stress. The core proteins of the Endosomal Sorting Complex Required for Transport (ESCRT) participate in exosome biogenesis and ILV‐mediated destruction of ubiquitinylated cargos. Accessory ESCRT‐III components have reported roles in ESCRT‐III‐mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 97 publications
1
34
0
Order By: Relevance
“…NTA of the particle size‐distribution showed that the particle size of sEV was in the range of 30–200 nm, similar to the findings of a previous study (Figure S5). 37 The results of TEM showed that sEV exhibited a characteristic globular morphology similar to reports in previous literature (Figure S6). 38 …”
Section: Resultssupporting
confidence: 86%
“…NTA of the particle size‐distribution showed that the particle size of sEV was in the range of 30–200 nm, similar to the findings of a previous study (Figure S5). 37 The results of TEM showed that sEV exhibited a characteristic globular morphology similar to reports in previous literature (Figure S6). 38 …”
Section: Resultssupporting
confidence: 86%
“…Larval haemocytes (Tassetto et al, 2017) Adaptive immune system Adult male secondary cells (Corrigan et al, 2014;Fan et al, 2020;Marie et al, 2023) Large MVBs: exosome subtype biogenesis; reproductive functions Adult muscle cells (Jewett et al, 2021) Neurodegeneration…”
Section: ++++ ++mentioning
confidence: 99%
“…Our analysis of APPL function has provided an explanation for the link between membranes and protein aggregation in SCs (Marie et al, 2023; Wells et al, 2023; Figure 8). APPL is the only APP-like homologue in flies; it is expressed at high levels in the nervous system, but is also transcribed in other tissues (Leader et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…Rab11-exosomes are a novel subtype of exosomes formed in compartments labelled by the recycling endosomal marker Rab11 (Fan et al, 2020), rather than by late endosomes, which were previously thought to be the key source of these secreted vesicles. Even though Rab11-exosomes may make up only a small proportion of cellular EV output, when their biogenesis is selectively inhibited, specific defects in physiological and pathological cell communication are observed (Marie et al, 2023). In SCs, Rab11-exosomes form in regulated secretory compartments, where they have an additional role, as evidenced by GAPDH2 knockdown, co-ordinately controlling with endosomal membranes the normal protein aggregation events required for large DCG biogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation